Fixed pitch size small-sided games in young soccer players: effects of different age categories and competitive levels on the physical and physiological responses - Cherni, Bilel; Marzouki, Hamza; Selmi, Okba; Gonçalves, Bruno; Chamari, Karim; Chen, Yung-Sheng; Bouassida, Anissa (Biology of Sport, 2025)
We compared the physical and physiological responses of young soccer players of different ages U13 (Under 13 years), U15, and U17 and competitive levels (elite and sub-elite) during fixed-pitch size smallsided games (SSGs) performed under different formats. In a cross-sectional design, seventy-two male players (12 players in each group) performed 3-a-side and 4-a-side SSGs with a fixed-pitch size (40×20 m). The total distance covered (TD), peak velocity (Vpeak), the distances covered at different running speed zones (0 to < 7.0, 7.0 to < 14.0, 14.0 to < 18.0, and ≥ 18.0 km.h −1 ), peak heart rate (HR peak ), HR mean , expressed as percentage of the theoretical HR max Theo, and blood lactate concentration post-SSGs (BLa) were recorded. Players in the 3-a-side SSGs covered more TD, distances covered at different speeds and Vpeak than those of the 4-a-side SSGs across all age categories of both competitive levels ( p < 0.05). The 3-a-side SSGs induced higher BLa in all elite groups ( p < 0.05), and U13-sub-elite players ( p =0.004). HR peak (%HR max Theo) and HR mean (%HR max Theo) were greater in the 4-a-side SSGs than the 3-a-side SSGs in most age categories of both competitive levels ( p < 0.05). In the zone-3, the U13- and U15-elite covered more distance than U17 in both formats. In both formats, elite players covered larger TD and distances at zone-1 and zone-4 sub-elite players ( p < 0.05). BLa was higher in U17-sub-elite compared to their elite counterparts in the 4-a-side SSGs. Our study shows that 3-a-side SSGs are physically more demanding than 4-a-side, especially for elite players. Tailoring training to age and competitive level is crucial for optimising player development.